Oncolytic viruses: adenoviruses - Niemann, Julia; Kühnel, Florian (Virus genes, 2017)
Tumor-selectively replicating (oncolytic) viruses are promising tools for therapy of solid cancers and have been initially developed to achieve potent tumor lysis with acceptable side effects on healthy tissue. However, in recent years, oncolytic viruses have been recognized as therapeutic vehicles exhibiting multipronged anti-tumoral activity. Apart from direct cytolysis, stimulation of both innate and adaptive tumor-directed immune responses have been recognized as important mechanisms of oncolytic virotherapy, which were probably decisive in achieving the long-term tumor remissions that oncolytic viruses have shown in clinical trials in advanced melanoma. In this short review, we will introduce basic mechanisms of viral oncolysis and the current state of clinical development. With a focus on oncolytic adenoviruses, we will describe the efforts to restrict oncolytic virus infection to tumor tissue using conditional replication and targeted delivery. Furthermore, we will discuss ways to optimize virus-mediated immunostimulation and the potential of virotherapy as an integrative part of systemic tumor immunotherapies.